SYN1 Mutation Causes X-Linked Toothbrushing Epilepsy in a Chinese Family - Zhou, Qin; Wang, Jingwei; Xia, Li; Li, Rong; Zhang, Qiumin; Pan, Songqing (Frontiers in Neurology, 2021)
Toothbrushing epilepsy is a rare form of reflex epilepsy (RE) with sporadic incidence. To characterize the genetic profile of reflex epilepsy patients with tooth brushing-induced seizures in a Chinese family. Solo clinical whole-exome sequencing (WES) of the proband, a 37-year-old Chinese man, was performed to characterize the genetic etiology of toothbrushing epilepsy. Mutations in the maternal X-linked synapsin 1 (SYN1) identified in the proband and his family members were confirmed by Sanger sequencing. The pathogenicity of these mutations was determined using in silico analysis. The proband had four episodes of toothbrushing-induced seizures. The semiology included nausea, twitching of the right side of the mouth and face, followed by a generalized tonic-clonic seizure (GTCS). The proband’s elder maternal uncle had three toothbrushing-induced epileptic seizures at the age of 26. The proband’s younger maternal uncle had no history of epileptic seizures but had a learning disability and aggressive tendencies. We identified a deleterious nonsense mutation, c.1807C>T (p.Q603Ter), in exon 12 of the SYN1 gene (NM_006950), which can result in a truncated SYN1 phosphoprotein with altered flexibility and hydropathicity. This novel mutation has not been reported in the 1000G, EVS, ExAC, gnomAD, or HGMD databases. We identified a novel X-linked SYN1 exon 12 mutant gene in a Chinese family that could be the underlying genetic basis for toothbrushing epilepsy. Our findings provide novel insights into the mechanism of this complex form of reflex epilepsy that could potentially be applied in disease diagnosis.